Age-Associated Changes to Lymph Node Fibroblastic Reticular Cells - Kwok, Tina; Medovich, Shannon C.; Silva-Junior, Ildefonso A.; Brown, Elise M.; Haug, Joel C.; Barrios, Marliece R.; Morris, Karina A.; Lancaster, Jessica N. (Frontiers in Aging, 2022)
The decreased proportion of antigen-inexperienced, naïve T cells is a hallmark of aging in both humans and mice, and contributes to reduced immune responses, particularly against novel and re-emerging pathogens. Naïve T cells depend on survival signals received during their circulation among the lymph nodes by direct contacts with stroma, in particular fibroblastic reticular cells. Macroscopic changes to the architecture of the lymph nodes have been described, but it is unclear how lymph node stroma are altered with age, and whether these changes contribute to reduced naïve T cell maintenance. Here, using 2-photon microscopy, we determined that the aged lymph node displayed increased fibrosis and correspondingly, that naïve T-cell motility was impaired in the aged lymph node, especially in proximity to fibrotic deposition. Functionally, adoptively transferred young naïve T-cells exhibited reduced homeostatic turnover in aged hosts, supporting the role of T cell-extrinsic mechanisms that regulate their survival. Further, we determined that early development of resident fibroblastic reticular cells was impaired, which may correlate to the declining levels of naïve T-cell homeostatic factors observed in aged lymph nodes. Thus, our study addresses the controversy as to whether aging impacts the composition lymph node stroma and supports a model in which impaired differentiation of lymph node fibroblasts and increased fibrosis inhibits the interactions necessary for naïve T cell homeostasis.